2022
DOI: 10.1159/000524883
|View full text |Cite
|
Sign up to set email alerts
|

Video Capsule Endoscopy after Bariatric Surgery: A Tertiary Referral Center Experience

Abstract: Background and aim: Minimal data is available regarding the performance of video capsule endoscopy (VCE) in patients that underwent bariatric surgery. We aim to report indications, feasibility and safety of VCE performed after bariatric surgery, specifically focusing on diagnosis rates of Crohn’s disease (CD) in this population. Methods: A retrospective analysis of all VCE procedures performed between January 2015 to December 2019. All patients that underwent bariatric surgery prior to VCE were included. Indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In bariatric patients presenting with iron deficiency anaemia, there is insufficient data to suggest whether video capsule endoscopy is safe for use. Peleg et al [4] demonstrated that video capsule endoscopy can potentially be used in patients post-sleeve gastrectomy with minimal adverse effects.…”
mentioning
confidence: 99%
“…In bariatric patients presenting with iron deficiency anaemia, there is insufficient data to suggest whether video capsule endoscopy is safe for use. Peleg et al [4] demonstrated that video capsule endoscopy can potentially be used in patients post-sleeve gastrectomy with minimal adverse effects.…”
mentioning
confidence: 99%